Detection and Quantification of X and Y sperms in Enriched Sahiwal Semen diluted in PBS using Raman Spectroscopy - Chaudhary, Deeksha; Rana, Meenakshi; Sharma, Mridula; Devlal, Kamal (The Indian Journal of Animal Reproduction, 2023)
The present study was undertaken to enrich X-sperms in Sahiwal bull semen by percoll density gradient method and to detect X and Y sperms in enriched semen by Raman spectroscopy. The experiment was performed at Semen Production Centre, CVASc, GBPUAT, Pantnagar, Uttarakhand. Ejaculates were collected by AV method from Sahiwal bull. X-sperm enrichment was done by the Percoll density gradient method. Three types of gradients were prepared i.e. 7 layers (70-10%), 7 layers (80-20%) and 3 layers (30%, 50% and 70%). Semen (1ml or 3ml) was placed over the gradient in a conical centrifuge tube. Centrifugation was done at 750 g (22-24°C) for 15 min. The pellets thus obtained were diluted in PBS medium. Raman spectroscopy was performed in different groups viz. fresh semen (Control), 3 layers (70%, 50% and 30% GI), 7 layers (70-10% GII), and 7 layers (80-20% GIII). Raman peaks (DNA specific) were not much clear for PBS diluted semen samples though intensities were highest for 7 layers (70-10%) among all groups. Thus semen enriched by the percoll-density gradient method (7 layers i.e. 70-10%) can be used to increase female calf birth after A.I.